Brand Image, Price, Product Quality And Their Relationship With Uniqlo Product Purchase Decision - Tasak, Ferdianty Rosalynda Rante; Dai, Bernard Limanto; Muchtar, Muchtar (Jurnal Economic Resource, 2024)
Study​ This aiming For analyze influence quality product , image brand , and price to decision purchase consumers , with studies case of Uniqlo brand customers . Research This use approach quantitative with collect data through questionnaire involving 102 respondents . Data analysis was carried out use device soft SmartPLS 4, which is based on Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis process involving measurement models For connect indicator with the constructs being measured , as well as the structural model For test connection between construct . Research results show that image brand and price own influence positive significant to decision purchase , while quality product No show significant influence . This is indicates that consumer more prioritize image brand and price in determine decision purchase they , compared quality product . Research This give implications important for Uniqlo party to Keep going increase image brand and maintain a competitive pricing strategy . Limitations study This covers focus on three variable main and approach quantitative which is not dig more in perception subjective consumers . Therefore that , it is recommended For do study advanced with add variable others , such as loyalty brands and promotions , as well as use approach mixture For produce more insight​ comprehensive